2015
DOI: 10.11564/29-2-757
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Use and Its Socio-economic Determinants among Women in North-East and North-West Regions of Nigeria: A Comparative Analysis

Abstract: This study investigated the socio-economic factors associated with reported contraceptive use by women of reproductive age in northern Nigeria. Bivariate and logistic regression analysis was applied to successive Nigeria Demographic and Health Survey (NDHS: 1999(NDHS: -2013 data to examine the relationship between reported use of modern contraceptives (the dependent variable) and the socio-economic status (age, rural-urban residence, education, religion, current work status, marital status, and number of livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…This is very important as the northern region suffers disparities in healthcare access 29,30 and is hesitant to some health policies because of religious, cultural practices and interpretations, and level of education. [31][32][33] Similarly, rural-urban variations in comprehensive HIV knowledge were observed in this study. Previous studies 16,34 have shown that young women in urban areas have higher odds of having comprehensive HIV knowledge compared with those in rural areas.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is very important as the northern region suffers disparities in healthcare access 29,30 and is hesitant to some health policies because of religious, cultural practices and interpretations, and level of education. [31][32][33] Similarly, rural-urban variations in comprehensive HIV knowledge were observed in this study. Previous studies 16,34 have shown that young women in urban areas have higher odds of having comprehensive HIV knowledge compared with those in rural areas.…”
Section: Discussionsupporting
confidence: 78%
“…This is very important as the northern region suffers disparities in healthcare access 29 , 30 and is hesitant to some health policies because of religious, cultural practices and interpretations, and level of education. 31 33 …”
Section: Discussionmentioning
confidence: 99%
“…The chance of being non-users is 0.6 times less for Catholics compared to Protestants. Certainly, the likelihood of being non-user was high among the young and women with no child, perhaps due to socio-religious prospects of having more children in the future (UNFPA, 2016;Godwin et al, 2015). The odds of using contraception increased strongly among urban women and those with much better education due to rapid social and economic changes underway in Rwanda (Ndaruhuye et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that women increase the use of contraceptives when they achieve their ideal number of children. Families also become even more challenging by more children for the associated additional expenses i.e., to provide better and higher education, food and clothing, shelter, and other health care services (Unumeri et al, 2015). Age at first cohabitation plays a significant importance in the problem of overpopulation.…”
Section: Discussion/analysismentioning
confidence: 99%